Neuro-cognition in patients of Obstructive Sleep Apnoea Syndrome - Rayees Ahmad Bhat; Masood Tanvir; Musharaf Bashir (National Scientific Medical Center, 2019)
Background: Obstructive Sleep Apnoea Hypoapnoea Syndrome (OSAHS) is known to be associated with impairment in neuro-cognitive functions. This impairment in cognition is associated with daytime sleepiness that results in occupational deficits and an increased risk of automobile accidents. Objectives: The aim of the study was to assess Neuro-cognition in patients of Obstructive Sleep Apnoea Hypoapnoea Syndrome (OSAHS)  Material and methods: Our study was an observational cross-sectional study. Eligible patients (n=205) undergoing polysomnography were categorized into Snoring (n=105), Mild OSA (n=70), Moderate OSA (n=17) and Severe OSA (n=13) groups, based on Apnoea Hypoapnoea Index (AHI). The Montreal Cognitive Assessment (MoCA) and the Mini-Mental State Examination (MMSE) Questionnaires were administered to assess their cognitive functions and the correlation between Questionnaire scores and severity of OSAS was determined. Results: MMSE Questionnaire detected overall cognitive impairment in 22% of OSA patients while as MoCA Questionnaire detected overall cognitive impairment in 33% of the same OSA patients. The frequency of mild neurocognitive impairment as detected by MMSE Questionnaire increased progressively as the severity of OSA increased from Snoring(6.7%) to Mild OSA(17.1%), Moderate OSA(29.4%) and severe OSA(38.4%). MoCA Questionnaire demonstrated the same pattern except that it was more sensitive. It detected cognitive impairment of 12.4% in Snoring group, 27.1% in Mild OSA group, 41.2% in Moderate OSA group and 53.9% in Severe OSA group. Conclusion: Neurocognitive impairment is common in patients with OSAHS. The MoCA is a more sensitive tool than MMSE for the assessment of mild cognitive impairment in OSAHS patients, whose performance on the MMSE is in the normal range.